Development and pilot evaluation of an evidence-based algorithm for MASLD (formerly NAFLD) management in primary care in Europe - Anastasaki, Marilena; Papadakis, Sophia; Gergianaki, Irini N.; Papastamatiou, Loucas; Aligizakis, Eftychios; Grillaki, Nikoleta; Boutzoukaki, Eleni; Sivaropoulos, Nektarios; Anastasiou, Foteini; Mendive, Juan; de Juan-Asenjo, Carlos; Hernández-Ibáñez, Rosario; et al. (Frontiers in Medicine, 2024)
Background Metabolic dysfunction-associated steatotic liver disease (MASLD, formerly NAFLD), emerges as major cause of morbidity and mortality globally, with chronic patients facing increased risk. Guidelines on MASLD management in primary care (PC) are limited. This study aimed to develop and evaluate a clinical care pathway for use in PC to improve MASLD screening and management, including early detection, communication and treatment, in three European countries (Greece, Spain, the Netherlands). Methods An international multidisciplinary panel of experts oversaw pathway development, which was designed as a two-step algorithm with defined and sequenced tasks. To evaluate algorithm implementation, a controlled pilot study was conducted. Patients at risk of MASLD were assigned to general practitioners (GPs) trained in algorithm implementation (active group) or usual care (control group) and followed for 4–8 weeks. Primary outcomes were the number of patients screened for MASLD, managed in PC and referred to specialists. Results In this algorithm, patients with metabolic or liver dysfunction, confirmed MASLD or cardiovascular disease are screened with FIB-4 and classified as having risk of low-level (FIB-4 < 1.3), intermediate-level (1.3 ≤ FIB-4 < 2.67) or high-level MASLD (FIB-4 ≥ 2.67). The algorithm provides evidence-based tools to support GPs manage patients with risk of low-level MASLD in PC, coordinate linkage of patients with risk of high-level MASLD to specialists and refer patients with risk of intermediate-level MASLD for elastography (low-risk if <7.9 kPa or intermediate/high-risk if ≥7.9 kPa). During pilot evaluation, N = 37 participants were recruited in Spain (54.1% women, median age: 63 years). Significantly higher rates of patients in the active group (n = 17) than the control group (n = 20) were screened with FIB-4 (94.1% vs. 5.5%, p = 0.004). Patients in the active group received significantly more frequently a PC intervention for weight loss (70.6% vs. 10.0%, p < 0.001), alcohol regulation (52.9% vs. 0%, p < 0.001) and smoking cessation (29.4% vs. 0%, p = 0.005). In Greece no algorithm implementation was observed in either the active or control group, while the evaluation was not conducted in the Netherlands for logistic reasons. Conclusion This study provides evidence on the development and implementation of a new PC algorithm for MASLD screening and management. Variations among participating settings in algorithm implementation are indicative of context-specific particularities. Further research is necessary for integrating such pathways in tailored interventions to tackle this emerging public health issue.